Relationships between diagnostic imaging of first carpometacarpal osteoarthritis and pain, functional status, and disease progression: A systematic review - Mazza, Dario F.; Boonsri, Pattira S.; Arora, Aman; Bayne, Christopher O.; Szabo, Robert M.; Chaudhari, Abhijit J.; Boutin, Robert D. (Osteoarthritis and cartilage, 2024)
To systematically review the association of pain, function, and progression in first carpometacarpal (CMC) osteoarthritis (OA) with imaging biomarkers and radiography-based staging. Database searches in PubMed, Embase, and the Cochrane Library, along with citation searching were conducted in accordance with published guidance. Data on the association of imaging with pain, functional status, and disease progression were extracted and synthesized, along with key information on study methodology such as sample sizes, use of control subjects, study design, number of image raters, and blinding. Methodological quality was assessed using National Heart, Lung, and Blood Institute tools. After duplicate removal, a total of 1969 records were screened. Forty-six articles are included in this review, covering a total of 28,202 study participants, 7263 with first CMC OA. Osteophytes were found to be one of the strongest biomarkers for pain across imaging modalities. Radiographic findings alone showed conflicting relationships with pain. However, Kellgren-Lawrence staging showed consistent associations with pain in various studies. Radiographic, sonographic, and MRI findings and staging showed little association to tools evaluating functional status across imaging modalities. The same imaging methods showed limited ability to predict progression of first CMC OA. A major limitation was the heterogeneity in the study base, limiting synthesis of results. Imaging findings and radiography-based staging systems generally showed strong associations with pain, but not with functional status or disease progression. More research and improved imaging techniques are needed to help physicians better manage patients with first CMC OA.